A novel coverless text information hiding method based on double-tags and twice-send. (11th February 2020) - Zhou, Xiang; Chen, Xianyi; Zhang, Fasheng; Zheng, Ningning
Recently, coverless text information hiding (CTIH) attracts the attention of an increasing number of researchers because of the high security. However, there are still many problems to be solved, for example the efficiency of retrieving and the hiding capacity. In the existing CTIH methods, the secret information is embedded to be one carrier with one label to ensure the success rate of information hiding. In this paper, we propose a novel CTIH method based on the double-tags and twice-send, in which the double tags in a text are achieved by designing the odd-even adjudgement, and a reverse index is created firstly to promote the efficiency of retrieving, then transform characters into binary numbers, which will be employed as the location tags to determine the secret information in the received texts. Finally, we improve the success rate of information hiding by sending the document twice. The experimental results show that the proposed method makes an improvement in the hiding capacity and efficiency compared with existing text CIH algorithms.